DEVELOPMENT OF ISLAMIC-INTEGRATED CHEMISTRY TEACHING MATERIALS ON CELL AND BIOMOLECULE MATERIALS - Buchori Muslim; Nahadi Nahadi; Sjaeful Anwar; Heli Siti Halimatul Munawaroh; Neng Sri Nuraeni (EDUSAINS, 2023)
Integration between science and Islam is still not maximally applied in Chemistry Education UIN Syarif Hidayatullah Jakarta. This is because learning facilities regarding Islam and science are still lacking. This study aims to develop an Islamic integrated enrichment book of chemistry which focus on structure and function of cells material. The method that used is 4STMD (Four Step Material Development). There were four steps conducted by the researcher, it was a selection, structuring, characterization, and reduction. The evaluation were carried out by the experts on Islamic integration material, using test cloze and intervention of feasibility test from language, presentation, performance, and graphics aspects. The results obtained at the selection stage are 12 of the 21 concepts declared feasible with the results of the percentage of material eligibility of 100%. At the structuring, 12 valid draft teaching materials were obtained. Validation result showed the appropriateness of each concept from the expert. Assessment for characterizatition test obtained an average of 12 concepts have a high level of understanding with 84,33% are belong in easy category. Feasibility test present a very good categorized which proven by the percentage 85,94%. The enrichment book can be used as a reference of integrated Islamic chemistry for students in Biochemistry courses, especially the material structure and function of cells in order to integrate Islamic science and science in daily life.